Feasibility and Safely of Oral Rehydration Therapy before Upper Gastrointestinal Endoscopic Submucosal Dissection - Yasutoshi Shiratori; Takashi Ikeya; Kenji Nakamura; Katsuyuki Fukuda (Gastroenterology Research and Practice)
Background/Aims. Preoperative oral rehydration therapy (PORT), often used before surgery, is rarely performed before endoscopy. Only a few reports of PORT before upper gastrointestinal endoscopy are available. This study is aimed at evaluating the safety and feasibility of PORT before upper gastrointestinal endoscopic submucosal dissection (ESD). Methods. We used alginade water (125 mL, Nestle Co., Kobe, Japan) for PORT. Alginade water is a flavored sports drink, which is palatable and promotes wound healing due to a high concentration of alginate. We conducted a single-center single-arm prospective feasibility study of PORT in 244 patients who underwent upper gastrointestinal ESD. The group wherein PORT was administered up to two hours before ESD (n=120) was compared with the historical control group (non-PORT group, n=120). We investigated the total fluid intake, hematocrit change, complications due to PORT, complications during ESD, ESD procedure time, and length of hospital stay in each group. Results. The average fluid intake in the PORT group was 462.6 mL. No complications were observed due to PORT and ESD, and significant differences in the ESD procedure time or hospital stay was not noted. Conclusion. PORT up to two hours before upper gastrointestinal ESD is feasible.